When healthcare leadership and philanthropy lead to an improved patient experience: The Paul Lepsoe Music Initiative - Sara Olivier; Corianne Bell; Cheryl Jones; Jerry M. Maniate (The Beryl Institute, 2022)
Through an unprecedented collaboration between an academic acute tertiary care hospital (The Ottawa Hospital (TOH) and a community-based professional orchestra (Ottawa Symphony Orchestra (OSO), the Paul Lepsoe Music Initiative represented an innovative partnership focused on improving patient care via (a) the integration of live music in waiting areas of the hospital's Cancer Center and (b) the creation of individualized music therapy interventions on the inpatient Palliative Care Unit. Patient, family, and volunteer/staff feedback further refined the intervention throughout the duration of the Initiative; a qualitative process that provided insight into the overall patient experience and opportunities for patients and families to inform practice. Hundreds of people at TOH were reached and better understood through this initiative. Results revealed that more than 85% enjoyed the music and believed music should be part of the care experience, suggesting that live music performance can be an effective, low-cost intervention to positively affect the hospital experience across multiple stakeholder groups. A powerful result of this partnership is that it contributed to the humanization of an often stressful and sterile environment through music; most especially, music that is light, optimistic, uplifting, simple and soothing, while also being consistent in texture, dynamics, and tempo. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens